(untitled) (Research, Society and Development, 2022)
The action of transforming medical education recommends active teaching-learning methodologies with student participation in the construction of knowledge. This process of change is based on national curriculum guidelines, as well as on the concept of health as a social phenomenon and on the consolidation of a single, quality health system. Objective: To report the experience of medicine professors at a university in the city of Rio de Janeiro. Method: This study is an experience report of first-term academics of the Discipline IESC1 of the Medicine Course at UNIGRANRIO. Results: The participation of medical students in the work process of the Family Health Teams (ESF), without distinction of functions or positions, in order to know the whole process and obtain significant learning focused on the reality experienced by USF professionals, ends up transforming this participation into a need to learn for them. Conclusion: The knowledge provided by the IESC discipline allows the student to develop skills to act in Primary Care in a critical and reflective way, in view of the possibility of confronting theory and practice.